Measurement and Sorting of MSMEs Business Performance Rating Using Analytical Hierarchy Process - Isnaeni Yuli Arini; Tiara Verita Yastica (International Journal of Innovation in Enterprise System, 2022)
This research was conducted in an enterprise that provides venture capital assistance to its 876 Micro,Small, and Medium Enterprises (MSME) partners to measure and sort the performance of theirbusiness. The enterprise wished for a business performance calculation system that is more reliableand utilized more than one criterion. In addition, the enterprise also desired to give rewards to MSMEswith the most excel accomplishment, so they need to know which MSMEs are the most developedamong others. This study uses focus group discussions and existing data to obtain the appropriateperformance measurement criteria. The determination of the weight of the importance of eachcriterion was carried out using the Analytical Hierarchy Process (AHP) method using pairwisecomparison techniques and its consistency is measured using the transitive property and consistencyratio. The proposed method is emphasized on ease of use and delivery to stakeholders but still capableof acquiring the performance calculation. The calculation includes the increase or decrease rate of thebusiness performance for each MSME, and after sorting the rating, the most accomplished MSMEalso can be found. The application of this method also can help the stakeholder to reach consensusswiftly.